THE RUPTURE PROCESS OF THE MW 7.8 CAPE KRONOTSKY, KAMCHATKA, EARTHQUAKE OF 5 DECEMBER 1997 AND ITS RELATIONSHIP TO FORESHOCKS AND AFTERSHOCKS - Zobin V.M.; Levina V.I. (My University, 2001)
A Mw 7.8 shallow subduction earthquake occurred on 5 December 1997 near Cape Kronotsky, Kamchatka Peninsula. Broadband P-wave inversions, carried out using two independent methods, allowed us to locate the position of the main asperities, one of high slip of up to 240 cm and a pair of lower slip, that ruptured during the mainshock. The mainshock hypocenter was located within the first asperity but not in the region of maximum slip. Most of the aftershock activity occurred within the low-slip asperities zone; the higher-slip asperity was characterized by low aftershock activity. All large aftershocks as well as the foreshocks (Mw ≥5.5) occurred outside of the asperities. The mainshock was preceded by a long-term series of single moderate-size events. Based on the spatial distribution of preceding events, foreshocks, aftershocks, and two main asperity zones broken during the mainshock, the following fault history of the Mw 7.8 earthquake is proposed. There was an asperity zone below the Kronotsky Cape and its submarine continuation. This asperity was the site of concentration of the events preceding the mainshock, the single earthquakes of magnitude mb between 5.5 and 6.1 that occurred during the 35 years before the mainshock of 5 December 1997. The Mw 5.8 earthquake of 9 February 1997, which was accompanied by aftershocks, finished this sequence of single events and marked a change in stress regime within the zone. A foreshock series occurred within the aftershock area of the 9 February earthquake, preparing the nucleus of rupture for the Mw 7.8 event, which began at the periphery of the Kronotsky asperity and then broke it almost completely. The rupture continued its way to the southwestern asperities. However, the southwestern asperities were only partially broken, with the amplitude of slip half that for the first asperity. As a result, during the aftershock stage, the maximum activity occurred around these asperity zones. The region of the first asperity, which was completely broken by the mainshock rupture, had almost no aftershock activity.